2022
DOI: 10.1002/dta.3241
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of five cannabinoids in blood and urine by gas chromatography tandem mass spectrometry applying automated on‐line solid phase extraction

Abstract: Cannabis is the most frequently consumed illegal substance worldwide. More recently, an increasing number of legal cannabis products low in psychoactive Δ 9 -tetrahydrocannabinol (THC) but high in non-intoxicating cannabidiol (CBD) are being more widely consumed. While the detection and quantification of THC and its metabolites in biological matrices is an important forensic-toxicological task, additional detection of CBD is also important, for example, when examining the plausibility of consumer's statements.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…The same happens when using systems with greater sensitivity, such as LC–MS/MS [ 38 , 39 , 40 , 42 , 45 , 46 , 47 , 48 , 49 ]. Nonetheless, some authors report lower LLOQs than those obtained with our MEPS–GC–MS, mostly using techniques with greater sensitivity, including GC–MS/MS [ 50 , 51 , 52 , 53 ] and LC–MS/MS [ 38 , 39 , 42 , 46 , 54 , 55 , 56 , 57 , 58 , 59 ]; several of these approaches also used larger sample volumes. Table 2 summarizes the information.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The same happens when using systems with greater sensitivity, such as LC–MS/MS [ 38 , 39 , 40 , 42 , 45 , 46 , 47 , 48 , 49 ]. Nonetheless, some authors report lower LLOQs than those obtained with our MEPS–GC–MS, mostly using techniques with greater sensitivity, including GC–MS/MS [ 50 , 51 , 52 , 53 ] and LC–MS/MS [ 38 , 39 , 42 , 46 , 54 , 55 , 56 , 57 , 58 , 59 ]; several of these approaches also used larger sample volumes. Table 2 summarizes the information.…”
Section: Resultsmentioning
confidence: 83%
“…Frozen urine samples were thawed at room temperature and centrifuged for 15 min at 4500 rpm before analysis. Authentic urine samples were hydrolyzed before extraction according to the literature [ 31 , 51 , 55 , 56 , 57 , 58 ]. Hydrolysis was performed by mixing urine (250 µL) with 10 µL of 10 M NaOH and incubating for 15 min at 60 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The percentage (%) recovery results (Table 2 ) obtained at each concentration level ranged between 97.1 and 99.1%, indicating insignificant interference from the excipients. Several authors have also reported acceptable accuracy ranging from 90 to 110% [ 42 , 55 ]. According to Kumar et al, acceptance criteria of accuracy range should at least be 80–120% of expected content [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ethanol is the most common analyte identified in forensic toxicology laboratories [38][39][40][41]. There are numerous analytical methods for determination of alcohol content from different alcoholic beverages already available worldwide [42,43]. However, in Botswana known alcohol concentrations are only limited to commercially sold drinks and excludes the homemade types.…”
Section: Number Of Deathsmentioning
confidence: 99%
“…For this reason, the determination of 11-nor-9-carboxy-THC (∆9-THC-COOH) in forensic toxicology laboratories is of special interest, to distinguish between the use of legal cannabis (mainly with CBD) and that of cannabis as a drug of abuse (mainly ∆9-THC, from which the inactive metabolite ∆9-THC-COOH is derived). This is especially important in countries where the use of high-CBD, low-THC cannabis products is legal to verify drug withdrawal [10].…”
Section: Introductionmentioning
confidence: 99%